PESAN TERSEMBUNYI DIBALIK LUKA: PENYEBAB PERILAKU SELF HARM PADA GENERASI Z - Avina Linda Setyowati; Mirna Nur Alia Abdullah; Muhammad Retsa Rizaldi Mujayapura (Yayasan Literasi Sains Indonesia, 2025)
Self harm is the behaviour of injuring oneself without suicidal intent. The act of self-harm became increasingly prevalent among teenagers, particularly within Generation Z. Generation Z grew up in an era of rapid technological advancement and social change, which resulted in significant social pressures. Self-harm was carried out for various reasons, one of which was as an attempt to express emotion, stress, depression and sadness that could not be conveyed. This article aimed to provide education regarding the factors contributing to self-harming behaviour among Generation Z. The method employed contributes to self-harm from the perspective of symbolic interactionism theory. The findings of this article highlight the factors that cause self-harm, including social pressure, both academic and non-academic, generation Z as victims of bullying, family disharmony, difficulties or problems in family, friendship or romantic relationships, loneliness and the influence of social interactions and social media. Unhealthy observations and interactions can trigger self-harm, as they can affect an individual’s thought patterns, leading them to engage in self-harming behaviour. Self-harm can be seen as a symbol carrying a specific meaning. It is often used as a means for individuals to express the pain they feel.